2020
DOI: 10.1088/1757-899x/888/1/012082
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of polypropylene fibres on the tensile performance of asphalt mixtures for road pavements

Abstract: The tensile strength of asphalt mixtures is one of the main parameters of deterioration and failure in flexible pavements. Hence, in this study, the effects of reinforcing asphalt mixtures, using polypropylene fibers, on their engineering performance were experimentally investigated. A set of cylindrical specimens of asphalt mixtures was prepared and subjected to a compressive load at different testing temperatures in terms of evaluation of the indirect tensile stiffness modulus. Similarly, fatigue (four-point… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…It is observed that there is an increment in the permeability value with the increase in the content of PP fiber. This is due to an increase in the PP fiber content increases the air content in the mixture volume [28]. However, the slight addition of PP fiber gave the least permeability value in the mixture.…”
Section: Water Permeabilitymentioning
confidence: 97%
“…It is observed that there is an increment in the permeability value with the increase in the content of PP fiber. This is due to an increase in the PP fiber content increases the air content in the mixture volume [28]. However, the slight addition of PP fiber gave the least permeability value in the mixture.…”
Section: Water Permeabilitymentioning
confidence: 97%
“…740 Several techniques have been applied in order to improve flexible pavements. During 744 bituminous mixture manufacturing, stiffness and cohesion can be developed by the addition of 745 fibres [138][139][140][141][142]. This is an effective technique to enhance pavement behaviour when they do 746 not meet traffic, climate and pavement structural requirements.…”
Section: Waste and By-products Materials Enhancement 676mentioning
confidence: 99%